Improvement of Electrochromic Stability of Viologen‐Based Ionic Gel by Layered Metal–Organic Frameworks - Huan Jiang; Yujiao Li; Fangfang Liu; Chenhao Wang; Liping Sheng; Jianfang Wang; Cheng‐an Tao (Advanced Materials Interfaces)
Abstract Metal–organic frameworks (MOFs) fulfill the requirements of electrochromic (EC) materials due to their unique 3D pore structure, excellent thermal stability, and outstanding processing and electrochemical properties. Viologens, a class of cationic organic molecules with remarkable redox properties, are a type of EC material with exceptional characteristics. In this study, ionic gel electrochromic materials are prepared by hybridizing zirconyl imine (ZrTCA) MOFs with ethyl viologen bis (trifluoromethane sulfonyl) imide (EV[TFSI]2) in varying proportions, and ionic gel electrochromic devices (ECDs) are constructed. The results indicate that the incorporation of layered zirconium‐based MOFs not only enriches the color states of the ionic gel ECDs but also transforms them from transparent to reflective displays. Compared to pure EV[TFSI]2 ECDs, those doped with zirconium MOFs exhibit a more uniform coloring state, shorter coloring time, higher coloration efficiency, and better cycle stability. This is attributed to the good chemical stability and efficient ion migration channels provided by the porous framework structure of zirconium‐based MOFs. Notably, the MOFs:EV[TFSI]2 (0.5:1) ECDs display a synergistic effect, with the redox cycle stabilizing for ≈1100 cycles and color bleaching kinetic stability tested up to 1600 switches, experiencing only a 9% reduction in ΔT, demonstrating significantly enhanced durability and stability compared to pure EV[TFSI]2 ECDs.